CD8+ T cell trajectory subtypes decode tumor heterogeneity and provide treatment recommendations for hepatocellular carcinoma - Liu, Long; Liu, Zaoqu; Gao, Jie; Liu, Xudong; Weng, Siyuan; Guo, Chunguang; Hu, Bowen; Wang, Zhihui; Zhang, Jiakai; Shi, Jihua; Guo, Wenzhi; Zhang, Shuijun (Frontiers in Immunology, 2022)
Introduction: Mounting evidence has revealed the interactions and dynamic alters among immune cells are critical to shaping tumor microenvironment (TME) and ultimately map onto heterogeneous clinical outcomes. Currently, the underlying clinical significance of immune cell evolutions remains largely unexplored in hepatocellular carcinoma (HCC). Methods: A total of 3817 immune cells and 1750 HCC patients of 15 independent public datasets were retrieved. The Seurat and Monocle algorithm were used to depict T cells evolution and Nonnegative matrix factorization (NMF) was further applied to identify molecular classification. Subsequently, the prognosis, biological characteristics, genomic variations, and immune landscape among distinct clusters were decoded. The clinical efficacy of multiple treatment approaches was further investigated. Results: According to trajectory genes expression, three heterogeneous clusters were identified with different clinical outcomes. C2 with more advanced pathological stage presented the most dismal prognosis relative to C1 and C3. Eight independent external cohorts validated the robustness and reproducibility of three clusters. Further explorations elucidated C1 characterized as lipid metabolic HCC and C2 referred to cell proliferative HCC, whereas C3 was defined as immune inflammatory HCC. Moreover, C2 also displayed the most conspicuous genomic instability and C3 deemed as ‘immune-hot’ performed abundant immune cells and elevated expression of immune checkpoints (ICPs). The assessments of therapeutic intervention suggested that patients in C1 were suitable for transcatheter arterial chemoembolization (TACE) treatment and patients in C2 were sensitive to tyrosine kinase inhibitors (TKIs), while patients in C3 were more responsive to immunotherapy. We also identified numerous underlying therapeutic agents, which might be conducive to clinical transformation in the future. Conclusions: Our study developed three clusters with distinct characteristics based on immune cell evolutions. For specifically stratified patients, we proposed individualized treatment strategies to improve clinical outcomes and facilitate clinical management.